2020
DOI: 10.1111/ppa.13279
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin induces bacterial pathogen resistance in tomato

Abstract: Phytohormones are involved in the regulation of plant responses to biotic stress. How a limited number of hormones differentially regulate defence responses and influence the outcome of plant–biotic interactions is not fully understood. In recent years, cytokinin (CK) was shown to induce plant resistance against several pathogens. In the present study, we investigated the effect of CK in inducing tomato resistance against the hemibiotrophic pathogenic bacteria Xanthomonas campestris pv. vesicatoria (Xcv) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…Why does CK directly inhibit growth and virulence of fungal pathogens from different classes (ascomycetes, basidiomycetes), different lifestyles (hemibiotrophs, necrotrophs), different modes of plant infection (air borne, soil borne, vascular or not) and different host target organs (leaves, stems, roots)? Of note is that us and others have found that CK has no direct inhibitory effect on bacterial pathogens (23, 40). Our results demonstrate that CK inhibits fungal growth and development ( Figs.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Why does CK directly inhibit growth and virulence of fungal pathogens from different classes (ascomycetes, basidiomycetes), different lifestyles (hemibiotrophs, necrotrophs), different modes of plant infection (air borne, soil borne, vascular or not) and different host target organs (leaves, stems, roots)? Of note is that us and others have found that CK has no direct inhibitory effect on bacterial pathogens (23, 40). Our results demonstrate that CK inhibits fungal growth and development ( Figs.…”
Section: Resultsmentioning
confidence: 84%
“…Given that CK can induce plant immunity and restrict phytopathogen growth in certain cases, direct effects of CK against phytopathogens are an intriguing possibility. A direct effect of CK on bacterial pathogens was ruled out in previous works (23, 25). Interestingly, CK did not affect germination and elongation of germ tubes, but strongly inhibited appressorium formation of Erysiphe graminis , an obligate biotrophic powdery mildew causing barley pathogen (14).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We and others have previously demonstrated that pathogenesis processes can activate the CK pathway [ 17 , 18 , 19 ], raising the possibility that CK pathway activation might be required for pathogen resistance. Interestingly, we previously found that B. cinerea infection activates the synthetic CK response promoter TCSv2 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In tobacco, an SA-independent, phytoalexin-dependent mechanism was reported [ 16 ]. We recently reported that CK induces systemic immunity in tomato, promoting resistance to fungal and bacterial pathogens in an SA- and ethylene (ET)-dependent mechanism [ 18 , 19 ]. Until recently, other than the evidence that SA is required for CK-induced immunity [ 14 , 15 , 17 ], and that phytoalexins are involved [ 16 ], no additional cellular mechanisms related to CK-mediated immunity had been reported.…”
Section: Introductionmentioning
confidence: 99%